Effect of the SIMS program on oral hygiene levels of 5–6-year-old children in the Kampar District, Malaysia: A cluster-randomized controlled trial - Anwar, Nurul Hayati; Nor, Nor Azlida Mohd; Yusof, Zamros Yuzadi Mohd (UI Scholars Hub, 2020)
Background: This study evaluated the effect of the “Senyuman Indah Milik Semua” program (SIMSP) versus the existing preschool oral healthcare program (POHP) on children’s oral health and parents’ oral health literacy (OHL) in Kampar district, Malaysia. Methods: This was a cluster-randomized, matched pair, examiner-blind, controlled trial. Using computer-generated random tables, 14 preschools were allocated to the SIMSP intervention over 6 months and another 14 were allocated to the POHP, which was concealed at the cluster level. Healthy 5–6-year-old children and parents who understood the Malay language were recruited. The SIMSP was comprised of preschool visits by dental therapists (DTs) who provided oral health education for children and parents. The POHP received visits from DTs only. The primary outcome was the dental plaque score. The secondary outcomes were children’s oral health behaviors and the parents’ OHL. Data were collected during February and October 2019 and analyzed using SPSS software. Results: Overall, 653 children were recruited (intervention: 344 vs. control: 309). At 6-months, 83.4% and 76.4% completed the study, respectively. The mean decrease in the plaque score was higher in the SIMSP than the POHP [p = 0.027, effect size (ES) = +0.51]. Significantly more SIMSP children consumed carbonated drinks ≤ 1–3 times/week (p = 0.033). Parents in the SIMSP had more knowledge (p = 0.024) with higher OHL scores (ES = +0.97) than parents in the POHP. Conclusion: The SIMSP was effective for reducing children’s plaque scores, soft drink intake, and improving parents’ OHL than POHP.